TINJAUAN HUKUM FUNGSIONALISASI PERTANAHAN DAN PENEGAKAN HUKUM TATA GUNA TANAH - Ahyuni Yunus (Fakultas Hukum Universitas Muhammadiyah Palu, 2020)
Allotment and use of land in a regional area has been determined in such a way as to spatial planning, both regional areas at the level of Regency / City, Province and national level. But along with the development developments carried out in all fields, land functionalization is often carried out which is no longer appropriate to its designation and use, causing damage or other impacts, law enforcement and land use implementation have not really been done or implemented, because other than the equipment -the rules of law that are not yet available, are also caused by inconsistencies of the relevant government officials. The designation and use of the land should remain consistent with the established land use, and the need for the application of strict sanctions to those who violate the provisions in the land use. Keyword: Land Functionalization, Law Enforcement, Land Use